2015
DOI: 10.1108/bepam-02-2014-0006
|View full text |Cite
|
Sign up to set email alerts
|

Case-based reasoning and BIM systems for asset management

Abstract: Purpose – The next generation of Building Information Modelling (BIM) seeks to establish the concept of Building Knowledge Modelling (BKM). The current BIM applications in construction, including those for asset management, have been mainly used to ensure consistent information exchange among the stakeholders. However, BKM needs to utilise knowledge management (KM) techniques into building models to advance the use of these systems. The purpose of this paper is to develop an integrated system t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 26 publications
(11 reference statements)
0
28
0
Order By: Relevance
“…Commonly established CAFM tools are: computer aided design (CAD) (ibid. ); integrated workplace management systems (IWMS) [28]; enterprise asset management (EAM) [29]; and computerized maintenance management systems (CMMS) [30]. Although these disparate tools have inherently different capabilities and functions, a vital prerequisite to implementing an appropriate CAFM system is that an organisation perceives data as its most invaluable asset [31].…”
Section: Facilities Management: Definitions Influences and Challengesmentioning
confidence: 99%
“…Commonly established CAFM tools are: computer aided design (CAD) (ibid. ); integrated workplace management systems (IWMS) [28]; enterprise asset management (EAM) [29]; and computerized maintenance management systems (CMMS) [30]. Although these disparate tools have inherently different capabilities and functions, a vital prerequisite to implementing an appropriate CAFM system is that an organisation perceives data as its most invaluable asset [31].…”
Section: Facilities Management: Definitions Influences and Challengesmentioning
confidence: 99%
“…BIM with its capabilities as a data conduit can provide an easy retrieval of the FM information required for senior management decisions. Current solutions include integrating BIM and FM systems' information using different technologies, such as semantic web technology, to help maintenance personnel to efficiently track and control the whole maintenance management process [72], and integrating BIM and knowledge systems in a case-based reasoning module to enable maintenance information retrieval and knowledge sharing to solve maintenance problems [73,74]. Other attempts focused on developing automated approaches to define possible causes and retrieve related information to facilitate the process of HVAC troubleshooting [75,76].…”
Section: Category: Maintenance Managementmentioning
confidence: 99%
“…Deployment of digital modelling in asset management can greatly improve the quality of data transfers between development stakeholders (Jiao et al, 2013;Lindkvist, 2015;Khaddaj and Srour, 2016). Traditional, manual handover of data often leads to inaccuracies (or worse, loss of data), diminishing the operational information held on a building during its lifecycle (Lindkvist, 2015;Motawa and Almarshad, 2015;Love et al, 2016a). Studies have shown that facility owners regularly encounter incomplete as-built data documentation, fostering dissatisfaction, particularly where transferred operations and maintenance (O&M) data proves wholly unsuitable for asset management (Mayo and Issa, 2016).…”
Section: Digital Asset Managementmentioning
confidence: 99%